2010
DOI: 10.1177/0961203309356456
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatitis as initial manifestation of systemic lupus erythematosus

Abstract: Pancreatitis as an initial manifestation of systemic lupus erythematosus is rare. Two cases are reported of young female patients who presented with fever, abdominal pain, vomiting and elevated levels of pancreatic enzymes. They were diagnosed with acute severe pancreatitis associated with systemic lupus erythematosus. There are a few reports in the literature about this association, but the pathogenesis and treatment are still controversial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 12 publications
0
31
0
Order By: Relevance
“…The cause of SLE‐pancreatitis has been attributed to a variety of mechanisms, including vasculitis, microthrombi formation related to antiphospholipid antibody, anti‐pancreatic antibodies and pancreatic inflammation due to T‐cell infiltration and complement activation 12 . However, microthrombi as the cause of pancreatitis was unlikely in the present patient because the tests for anti‐phospholipid antibodies were negative.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…The cause of SLE‐pancreatitis has been attributed to a variety of mechanisms, including vasculitis, microthrombi formation related to antiphospholipid antibody, anti‐pancreatic antibodies and pancreatic inflammation due to T‐cell infiltration and complement activation 12 . However, microthrombi as the cause of pancreatitis was unlikely in the present patient because the tests for anti‐phospholipid antibodies were negative.…”
Section: Discussionmentioning
confidence: 67%
“…In an SLE patient who is unresponsive to the standard line of drug treatment, including adequate doses of glucocorticoids, then high‐dose intravenous immunoglobulin or cytotoxic agents like cyclophosphamide are recommended 12,29 . The patient presented in this report was treated accordingly (high dose i.v.‐cyclophosphamide) with excellent response.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Gastrointestinal (GI) manifestations are common in SLE patients, but acute pancreatitis is rare [16]. It was reported that 19.2%–50% of SLE patients presented with gastrointestinal symptoms [7–11], whereas pancreatitis occurred in about 0.7%–8.2% of patients with SLE [7, 8, 11, 12] and the annual incidence was approximately 0.4–1.1‰ [35].…”
Section: Introductionmentioning
confidence: 99%
“…[469][470][471][472][473][474] Lupus mesenteric vasculitis (LMV), a leukocytoclastic vasculitis of mesenteric vessel walls, also known as lupus enteritis, usually presents with abdominal pain, sometimes associated with impaired intestinal motility and signs of peritonitis. The most frequent symptoms in both adults in children are abdominal pain, nausea, vomiting, and fever.…”
Section: Cytopenia Type Frequency Key Laboratory Features Managementmentioning
confidence: 99%